Formas de subjetivação da Geração Y - Verzoni, André (2015)
This master thesis consists of two articles. The first article is a theoretical study, while the second is an empirical article. The primary objective of this thesis was to investigate and understand the subjectivity of the Generation Y. The theoretical paper, structured as a nonsystematic review, proposes a discussion of the subjectivity established by the Generation Y considering their integrants agents and subjects of the contemporary time. The empirical article is the result of a qualitative, exploratory and cross-sectional research, which goal is the description and understanding of the subjectivity presented by the Generation Y. To achieve this purpose, semi-structured interviews with open exploratory axis were made. The themes of the interview were: work, interpersonal and virtual relationships, self and others image, time (routine), ethical ideals, idols (celebrities), violence, consumption, goals and critical about contemporary society. The method used to analyze the content of the interviews was the Interpretative Analysis proposed by Frederick Erickson. The conclusions were that the Generation Y present ambivalence, idealism and the persistence of adolescent traits; propose various critics and demands towards the context where they live and have high expectations about themselves; consider the collective and creative work the key to professional achievement; maintain that experience other cultures is vital for personal development and classify the lack of respect for individuality one of the most reprehensible forms of violence.